Efficient and Stable CsPbI3 Inorganic Perovskite Photovoltaics Enabled by Crystal Secondary Growth. Issue 44 (13th September 2021) - Wang, Xingtao; Wang, Yong; Chen, Yuetian; Liu, Xiaomin; Zhao, Yixin
Abstract: Defect‐triggered phase degradation is generally considered as the main issue that causes phase instability and limited device performance for CsPbI3 inorganic perovskites. Here, a defect compensation in CsPbI3 perovskite through crystal secondary growth of inorganic perovskites is demonstrated, and highly efficient inorganic photovoltaics are realized. This secondary growth is achieved by a solid‐state reaction between a bromine salt and defective CsPbI3 perovskite. Upon solid‐state reaction, the Br − ions can diffuse over the entire CsPbI3 perovskite layer to heal the undercoordinated Pb 2+ and conduct certain solid‐state I/Br ion exchange reaction, while the organic cations can potentially heal the Cs + cation vacancies through coupling with [PbI6 ] 4− octahedra. The carrier dynamics confirm that this crystal secondary growth can realize defect compensation in CsPbI3 . The as‐achieved defect‐compensated CsPbI3 not only improves the charge dynamics but also enhances the photoactive phase stability. Finally, the CsPbI3 ‐based solar cell delivers 20.04% efficiency with excellent operational stability. Overall, this work proposes a novel concept of defect compensation in inorganic perovskites through crystal secondary growth induced by solid‐state reaction that is promising for various optoelectronic applications. Abstract : Defect‐triggered phase degradation has become the main issue in the field of inorganic CsPbI3 perovskite. A crystal secondary growth of inorganic perovskites induced by a solid‐state reaction to achieve defect compensation in CsPbI3 perovskite is demonstrated. Finally, the defect‐compensated CsPbI3 ‐based solar cell delivers 20.04% efficiency with excellent operational stability.